PENGARUH PENYARADAN KAYU DENGAN TRAKTOR RANTAI KELABANG TERHADAP PENGGESERAN DAN PEMADATAN TANAH HUTAN - Maman Mansyur Idris; Yahya Fakuara; Gunarwan Suratmo; Rahardjo S Suparto (Jurnal Penelitian Hasil Hutan, 1988)
The study  of  the  effect of  log skidding  by crawler   tractors  on  forest soil displacement  and compaction wall carried out in one logging company in West Kalimantan in 1986.                                                                                                    The  results  of  the study  are as the following  :The  average  volume   of  soil  displacement was 0.06   cu.m/m  of  skid  road,  it  i6 equal  to  0.061 ton/sq.m. This level of soil displacement iis higher  than  the  soil loss tolerance of  0.0002   ton/sq.m.Soil  compaction as indicated  by the average soil bulk  density is  0.16 g/cu.cm.  At this level of compaction, the porosity is 56%  (far  higher  than  10%  minimum   porosity), which  means  that  the growth  of  vegetation   will be still  favourable.The role of  soil  water  content and  slope on forest soil displacement was positively   significant. The  role of skidding intensity on forest  soil  compaction   was positively   significant   and  the  role  of soil  water  content   and slope  on forest soil  compaction was negatively  significant.